Development of an immunodeficient mouse that allows for conditional ablation of monocytic cells - Hui, Alvin J.; Lai, Kelly; Doyle, Eva H.; Rivera-Torruco, Guadalupe; Gutierrez, Alan G.; Du, Emily J.; Meijer, Yarah B. M.; Smith, Gabrielle; Gilfanova, Renata; Chung, Kenton G.; Auclair, Kirsten M.; Milani, Pamela; et al. (Frontiers in Immunology, 2025)
Background and aimsImmunodeficient mice, like the NOD-SCID-Gamma (NSG) strain, are important for the study of xenogeneic cells because of their lack of lymphocytes, dysfunctional hemolytic complement factor 5 (C5), and macrophage defects making them permissive hosts. Nonetheless, cellular barriers remain that limit engraftment of foreign cells such as monocytic phagocytes. Accordingly, we created a line of mice that allows for depletion of monocytic cells by breeding NSG mice with macrophage Fas-induced apoptosis (MaFIA) mice resulting in a stable line of NSG-MaFIA mice.MethodsNSG-MaFIA mice were generated by crossing NSG and MaFIA mice, with the hybrids backcrossed for nine generations to NSG mice. Flow cytometry was used to detect the expression of the MaFIA gene construct among blood leukocytes. Functional and confirmatory studies evaluated the successful transfer of the MaFIA transgene into the NSG genetic background. Apoptosis of monocytic cells was achieved through administration of a homodimerizer drug. The phenotypic characteristics of NSG mice were confirmed in NSG-MaFIA mice by flow cytometry, CBC analysis, testing of radiation sensitivity, and sequencing of the C5 gene. The permissiveness of NSG-MaFIA mice for xenogeneic engraftment was tested by transfusion of human red blood cells (RBCs) and peripheral blood mononuclear cells (PBMCs).ResultsThe MaFIA transgene was hybridized into NSG mice as exhibited by expression of a fluorescent marker. Functional expression of the MaFIA transgene was evidenced by weight loss and decreased fluorescence after homodimerizer treatment. NSG-MaFIA mice are lymphopenic, are sensitive to X-ray irradiation, and carry a mutated C5 gene. Transfusion of human RBCs resulted in similar clearance in NSG and NSG-MaFIA mice, without homodimerizer treatment, indicating a similar innate immune response. Moreover, transfusion of human RBCs or PBMCs after depletion of monocytic cells led to prolonged circulation of RBCs and rapid engraftment of leukocytes.ConclusionsA novel NSG-MaFIA mouse line was developed that has use in the study of monocytic cells and in the development of better humanized mouse models. Transfusion of human blood cells into cell-depleted NSG-MaFIA mice increased the persistence of the human cells in the circulation, indicating a role for monocytic cells in the removal of xenogeneic cells from immunodeficient mice.